Hot stamping part

By controlling the components and microstructure of the steel plate for hot stamping, the problem of deterioration in mechanical properties caused by regional strength differences in hot stamping components is solved, and the molded parts after hot stamping are achieved with high strength and high toughness.

CN119630829APending Publication Date: 2025-03-14HYUNDAE STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280098681.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2022-12-01
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In hot stamping parts, due to differences in regional strength caused by components and microstructure in the steel plate, the mechanical properties of molded parts after hot stamping are deteriorated.

Method used

By controlling the components and microstructure of the content of the steel plate for hot stamping, the steel plate contains appropriate amounts of carbon, silicon, manganese, chromium, boron, molybdenum, titanium, niobium, vanadium and other elements, and forms appropriate austenite grains and carbon-based precipitates, ensuring that the molded parts of the steel plate after hot stamping have high strength and high toughness.

Benefits of technology

The molded parts after hot stamping have excellent mechanical properties, such as high tensile strength, high yield strength and good bending properties, meeting the requirements of tensile strength of 1700MPa or more and yield strength of 1150MPa or more.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630829A_ABST
    Figure CN119630829A_ABST
Patent Text Reader

Abstract

According to one aspect of the present invention, there is provided a hot-stamped component comprising a steel sheet comprising: 0.26 wt% to 0.40 wt% of carbon (C); 0.02 wt% to 2.0 wt% of silicon (Si); 0.3 wt% to 1.60 wt% of manganese (Mn); up to 0.03% by weight of phosphorus (P); up to 0.008% by weight of sulfur (S); 0.05 wt% to 0.90 wt% of chromium (Cr); from 0.0005% to 0.01% by weight of boron (B); from 0.05% to 0.2% by weight of molybdenum (Mo); 0.001 wt% to 0.095 wt% of titanium (Ti); 0.001 wt% to 0.095 wt% of niobium (Nb); 0.001% to 0.095% by weight of vanadium (V); a hot-stamped part having a tensile strength of at least 1700 MPa and a yield strength of at least 1150 MPa, in which the hot-stamped part has a microstructure containing austenitic grains and including a carbon-based precipitate containing at least one of niobium (Nb), titanium (Ti), molybdenum (Mo), and vanadium (V), the carbon-based precipitate containing at least one of niobium (Nb), titanium (Ti), molybdenum (Mo), and vanadium (V), and the balance being iron (Fe) and other unavoidable impurities, the hot-stamped part having a tensile strength of at least 1700 MPa and a yield strength of at least 1150 MPa. And the average size of the austenite grains is at most 15 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to a hot stamping component, and more particularly, to a hot stamping component in which a molded component after hot stamping has excellent mechanical properties, such as high strength and high toughness. Background Art

[0002] In order to achieve lightness and stability, high-strength steel is used in vehicle parts. At the same time, high-strength steel can obtain high strength characteristics compared to weight, but as the strength increases, the stamping formability will deteriorate, causing the material to break or rebound during processing, making it difficult to form products with complex and precise shapes.

[0003] Hot stamping is a method to improve these problems, and as interest in this method increases, research on materials for hot stamping is also actively being conducted. For example, as disclosed in Korean Patent Publication No. 10-2017-0076009, the hot stamping method is a forming technology for manufacturing high-strength parts, which is to heat the steel sheet for hot stamping to a high temperature and then quickly cool the steel sheet while forming the steel sheet in a stamping die.

[0004] In addition, as disclosed in Korean Patent Publication No. 10-2019-0095858, so-called boron steel (22MnB5) (containing carbon (C) and manganese (Mn), boron (B), etc. as elements for improving heat treatment properties) is used as a typical example of a steel sheet for hot stamping. Summary of the invention

[0005] Technical issues

[0006] However, in the hot stamping parts according to the related art, there is a problem that the mechanical properties (such as tensile strength, bending properties, etc.) of the molded parts after hot stamping deteriorate due to the strength difference between regions generated by the components and microstructures contained in the steel sheet for hot stamping.

[0007] In order to solve various problems including the above problems, embodiments of the present invention are intended to provide a hot stamping part, wherein the molded part after hot stamping has excellent mechanical properties (such as high strength and high toughness). However, such a goal is only an example, and the scope of the present invention is not limited thereto.

[0008] Solution to the problem

[0009] According to one aspect of the present invention, there is provided a hot stamping component, the hot stamping component comprising a steel plate, the steel plate comprising: 0.26 wt% to 0.40 wt% carbon (C), 0.02 wt% to 2.0 wt% silicon (Si), 0.3 wt% to 1.60 wt% manganese (Mn), 0.03 wt% or less phosphorus (P), 0.008 wt% or less sulfur (S), 0.05 wt% to 0.90 wt% chromium (Cr), 0.0005 wt% to 0.01 wt% boron (B), 0.05 wt% to 0.2 wt% molybdenum (Mo), 0.001 wt% % to 0.095 wt % of titanium (Ti), 0.001 wt % to 0.095 wt % of niobium (Nb), 0.001 wt % to 0.095 wt % of vanadium (V), and the balance of iron (Fe) and other inevitable impurities, the hot stamping part having a tensile strength of 1700 MPa or more and a yield strength of 1150 MPa or more, wherein the hot stamping part comprises a microstructure, the microstructure comprising austenite grains and carbon-based precipitates, the carbon-based precipitates containing at least one of niobium (Nb), titanium (Ti), molybdenum (Mo) and vanadium (V), and the average size of the austenite grains is 15 μm or less.

[0010] Advantageous Effects of the Invention

[0011] According to the above-configured embodiment of the present invention, a hot stamping component can be realized, wherein the molded component after hot stamping has excellent mechanical properties (eg, high strength, high toughness, etc.).

[0012] Specifically, by controlling the components, microstructures, and properties of precipitates contained in the hot stamping steel sheet to adjust the strength difference between regions of the hot stamping steel sheet, a hot stamping steel sheet and a method for manufacturing the same can be realized, wherein the molded part of the hot stamping steel sheet has excellent mechanical properties (e.g., high strength, high toughness, etc.) after hot stamping. According to the embodiment of the present invention, the scope of the present invention is not limited to the above-mentioned effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is an image showing a portion of the microstructure of a steel sheet before hot stamping according to an embodiment of the present invention.

[0014] Figure 2 To show that according to Figure 1 An image of the structure of a hot stamped part formed by hot stamping a steel plate.

[0015] Figure 3 and Figure 4Graphs showing the results of measuring austenite grain size and fraction of hot stamped parts according to an embodiment of the present invention and comparative examples. DETAILED DESCRIPTION

[0016] Best Mode for Carrying Out the Invention

[0017] According to an embodiment of the present invention, the fraction of austenite grains having a size of 10 μm or more is 67% or less.

[0018] According to an embodiment of the present invention, the fraction of austenite grains having a size of 20 μm or more is 10% or less.

[0019] According to an embodiment of the present invention, when the contents of titanium (Ti), niobium (Nb), vanadium (V), and molybdenum (Mo) contained in the steel sheet may be represented by [Ti], [Nb], [V], and [Mo] in weight %, respectively, the following [Inequality 1] may be satisfied,

[0020] [Inequality 1]

[0021] 0.015≤0.25([Ti]+[Nb]+[V]+0.25[Mo])≤0.060 (unit: weight %).

[0022] According to an embodiment of the present invention, the amount of active hydrogen of the hot stamped part may be 0.6 wppm or less.

[0023] According to an embodiment of the present invention, the average particle size of the precipitates may be 10 nm or less.

[0024] According to an embodiment of the present invention, the precipitate may include 50 wt % or less of titanium (Ti) and 30 wt % or more of molybdenum (Mo).

[0025] According to an embodiment of the present invention, the average number of precipitates per unit area may be 10,000 / 100 μm 2 Up to 35,000 / 100μm 2 .

[0026] According to an embodiment of the present invention, the average gap between precipitates may be 0.1 nm to 100 nm.

[0027] According to an embodiment of the present invention, the hot stamping part can satisfy a bending angle of 50° or more.

[0028] Other aspects, features, and advantages, in addition to those described above, will become apparent from the following drawings, claims, and detailed description of the invention.

[0029] Mode for Carrying Out the Invention

[0030] Various modifications may be made to the embodiments of the present invention, and specific embodiments will be illustrated in the accompanying drawings and described in the detailed description section. The effects and features of the embodiments of the present invention and the methods for achieving these effects and features will become clearer with reference to the detailed description of the accompanying drawings below. However, the embodiments of the present invention may be implemented in various forms, and are not limited to the embodiments set forth below.

[0031] In the following embodiments, it will be understood that although the terms first, second, etc. are used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element.

[0032] In the following embodiments, as used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0033] In the following embodiments, it will be further understood that when the terms “include” and / or “comprising” are used in this specification, the presence of the components or elements is specified, but the presence or addition of one or more other components or elements is not excluded.

[0034] For the convenience of explanation, the size of each element in the drawings may be exaggerated. For example, since the size and thickness of the elements in the drawings are arbitrarily described for the convenience of explanation, the following embodiments are not limited thereto.

[0035] When a certain embodiment can be implemented in different ways, a specific process order can be performed in a different order than the described order. For example, two processes described in succession can be performed substantially simultaneously or in an order opposite to the described order.

[0036] In the specification, expressions such as "A and / or B" may include A, B, or A and B. In addition, expressions such as "at least one of A and B" may include A, B, or A and B.

[0037] Hereinafter, the embodiments will be described in detail with reference to the accompanying drawings, and in the description with reference to the accompanying drawings, the same or corresponding components are denoted by the same reference numerals, and redundant descriptions thereof are omitted.

[0038] Figure 1 is an image showing a portion of the microstructure of a steel sheet before hot stamping according to an embodiment of the present invention.

[0039] Specifically, Figure 1 A hot stamping steel sheet is shown, which is controlled and manufactured so that the material content forming the hot stamping steel sheet, the configuration of the microstructure of the hot stamping steel sheet, and the process conditions for manufacturing the hot stamping steel sheet meet preset conditions.

[0040] The steel plate according to the embodiment of the present invention may be a steel plate manufactured by subjecting a cast slab to a hot rolling process and / or a cold rolling process to contain a predetermined content of certain alloy elements.

[0041] The steel plate may contain carbon (C), silicon (Si), manganese (Mn), phosphorus (P), sulfur (S), chromium (Cr), boron (B), calcium (Ca), molybdenum (Mo), titanium (Ti), niobium (Nb), vanadium (V), the balance of iron (Fe) and other inevitable impurities. In one embodiment, the steel sheet for hot stamping may include carbon (C) in an amount of 0.26 wt% to 0.40 wt%, silicon (Si) in an amount of 0.02 wt% to 2.0 wt%, manganese (Mn) in an amount of 0.3 wt% to 1.60 wt%, phosphorus (P) in an amount of 0.03 wt% or less, sulfur (S) in an amount of 0.008 wt% or less, chromium (Cr) in an amount of 0.05 wt% to 0.90 wt%, boron (B) in an amount of 0.0005 wt% to 0.01 wt%, molybdenum (Mo) in an amount of 0.05 wt% to 0.2 wt%, titanium (Ti) in an amount of 0.001 wt% to 0.095 wt%, niobium (Nb) in an amount of 0.001 wt% to 0.095 wt%, vanadium (V) in an amount of 0.001 wt% to 0.095 wt%, and the balance of iron (Fe) and other inevitable impurities. In addition, the steel sheet for hot stamping may further include calcium (Ca) in an amount of 0.00001 wt % to 0.0060 wt %, selectively.

[0042] Carbon (C) plays the role of an austenite stabilizing element in the steel sheet. Carbon is the main element that determines the strength and hardness of the steel sheet, and the purpose of adding carbon can be to improve hardenability and strength during heat treatment. The amount of carbon included can be 0.26 wt % to 0.40 wt % based on the total weight of the steel sheet. When the carbon content is less than 0.26 wt %, it is difficult to obtain a hard phase (such as martensite, etc.), which may make it difficult to meet the mechanical strength of the molded parts after hot stamping. In contrast, a carbon content exceeding 0.40 wt % may cause the machinability of the steel sheet to deteriorate or the bending performance of the molded parts after hot stamping to deteriorate.

[0043] Silicon (Si) plays the role of a ferrite stabilizing element in the steel sheet. As a solid solution strengthening element, silicon improves the strength of the steel sheet and limits the formation of low-temperature carbides, thereby increasing the carbon concentration in austenite. In addition, silicon is also a core element in hot rolling, cold rolling, hot pressing structural homogenization and fine dispersion of ferrite. Silicon plays the role of a martensite strength uneven control element to improve crashworthiness. Based on the total weight of the steel sheet, the amount of silicon included can be 0.02 wt % to 2.0 wt %. When the silicon content is less than 0.02 wt %, it may be difficult to achieve the above effect, and cementite formation and coarsening may occur in the martensitic structure of the molded part after hot stamping. In contrast, when the silicon content exceeds 2.0 wt %, the hot rolling load and the cold rolling load may increase, and the plating performance of the steel sheet may deteriorate.

[0044] Meanwhile, when silicon (Si) is appropriately added in an amount of 0.3 wt % or more, a pearlite region with the lowest content can be formed in the hot stamping steel sheet by suppressing excessive formation of a pearlite region where pearlite is accumulated in the hot stamping steel sheet.

[0045] Manganese (Mn) plays the role of austenite stabilizing element in steel sheet. The purpose of adding manganese is to improve hardenability and strength during heat treatment. Based on the total weight of the steel sheet, the amount of manganese included can be 0.3 wt % to 1.60 wt %. When the manganese content is less than 0.3 wt %, the hardenability effect is insufficient, so the hard phase fraction in the molded part after hot stamping may be insufficient due to insufficient hardenability. In contrast, when the manganese content exceeds 1.60 wt %, there will be a region where manganese segregation pearlite is concentrated, which may cause ductility and toughness to decrease, which leads to a decrease in the bending performance of the molded part after hot stamping and produces an uneven microstructure.

[0046] Phosphorus (P) is an element that helps improve strength. Phosphorus may be included in an amount of greater than 0 wt% to 0.03 wt% or less based on the total weight of the steel plate to prevent the toughness of the steel plate from decreasing. When the phosphorus content exceeds 0.03 wt%, iron phosphide compounds are formed, thereby decreasing toughness and weldability, and cracks may be generated in the steel plate during the manufacturing process.

[0047] Sulfur (S) is an element that helps improve machinability. Sulfur may be included in an amount of greater than 0 wt% to 0.008 wt% or less based on the total weight of the steel plate. When the sulfur content exceeds 0.008 wt%, hot workability, weldability, and impact resistance may be reduced, and surface defects such as cracks may occur due to the generation of large inclusions.

[0048] The purpose of adding chromium (Cr) is to improve hardenability and strength during heat treatment. Chromium can refine grains and ensure strength by precipitation hardening. The amount of chromium included can be 0.05 wt % to 0.9 wt % based on the total weight of the steel sheet. When the chromium content is less than 0.05 wt %, the precipitation hardening effect may be reduced. In contrast, when the chromium content exceeds 0.9 wt %, the content of Cr-based precipitates and matrix solid solution increases, resulting in reduced toughness, and the production cost may increase due to increased costs.

[0049] The purpose of adding boron (B) (ensuring martensitic structure by limiting ferrite, pearlite and bainite transformation) is to obtain hardenability and strength during heat treatment. In addition, boron segregates at grain boundaries and reduces grain boundary energy, thereby improving hardenability, and has the effect of grain refinement by increasing austenite grain growth temperature. In terms of the gross weight of the steel plate, the amount of boron included can be 0.0005 wt % to 0.01 wt %. When the included boron is within the above range, hard phase grain boundary brittleness can be prevented, and high toughness and bendability can be ensured. When the boron content is less than 0.0005 wt %, the hardenability effect is insufficient. In contrast, when the boron content exceeds 0.01 wt %, the solid solubility is low, so boron is easily precipitated at the grain boundary according to the heat treatment conditions, which causes hardenability to decline or high temperature embrittlement, and due to the occurrence of hard phase grain boundary brittleness, toughness and bendability may decline.

[0050] Calcium (Ca) may be added to control precipitates. Calcium has a high bonding strength with sulfur, thereby forming CaS precipitates, which can suppress the generation of MnS that hinders weldability. The amount of calcium included may be 0.00001 wt % to 0.006 wt % based on the total weight of the steel sheet. When the calcium content is less than 0.00001 wt %, the MnS control effect deteriorates. When the calcium content exceeds 0.006 wt %, the continuous casting performance may deteriorate.

[0051] Titanium (Ti) can effectively promote grain refinement by forming precipitates at high temperatures. Based on the total weight of the steel plate, the amount of titanium included can be 0.001 wt % to 0.095 wt %, particularly 0.005 wt % to 0.06 wt %. When the titanium included is within the content range, continuous casting defects and precipitate coarsening can be prevented, the physical properties of the structural steel can be easily ensured, and defects such as cracks on the surface of the structural steel can be prevented. When the titanium content is lower than the lower limit, the appropriate effect may not be achieved. In contrast, when the titanium content exceeds the upper limit, the precipitate becomes coarse, so that the elongation and bendability may decrease.

[0052] Niobium (Nb) and vanadium (V) can increase strength and toughness according to the reduction of the size of martensite lath bundles. The amount of niobium and vanadium contained can be 0.005 wt% to 0.06 wt% respectively based on the total weight of the steel plate. When the niobium contained is within the above range, the grain refining effect of the steel plate is excellent during hot rolling and cold rolling, cracks in the slab and brittle fracture of the product can be prevented during steelmaking / continuous casting, and the generation of coarse precipitates during steelmaking can be minimized. When the niobium content is less than 0.005 wt%, appropriate effects may not be achieved. In contrast, when the niobium content exceeds 0.06 wt%, the strength and toughness are not further improved with the increase of the niobium content, and the niobium exists in the ferrite in the state of use, so there is a risk that the impact toughness may be greatly reduced. Vanadium may also have a tendency similar to that of niobium described above.

[0053] Molybdenum (Mo) is used as a substitute element to improve the strength of steel through solid strengthening. The purpose of adding molybdenum can be to reduce the roughness of precipitates and improve hardenability. In addition, molybdenum (Mo) can be used to improve the hardenability of steel. Based on the gross weight of the steel plate, the amount of molybdenum included can be 0.05 wt % to 0.2 wt %. When the molybdenum content is less than 0.05 wt %, a suitable effect can be achieved. In contrast, when the molybdenum content exceeds 0.2 wt %, there is a risk of reducing rolling productivity and elongation, and only manufacturing costs will be increased without additional impact.

[0054] The above-mentioned titanium (Ti), niobium (Nb), vanadium (V) and molybdenum (Mo) can be used as elements for controlling the formation of precipitates in molded parts after hot stamping. In one embodiment, the steel sheet may appropriately contain titanium (Ti), niobium (Nb) and vanadium (V), and the amount is 0.005 wt % to 0.06 wt %, respectively. Therefore, when the amount of titanium (Ti), niobium (Nb) and vanadium (V) contained is 0.005 wt % to 0.06 wt %, respectively, and the amount of molybdenum (Mo) contained is 0.05 wt % to 0.2 wt %, the microstructure area of ​​the steel sheet before hot stamping can be easily controlled, and in addition, the condition of easily controlling the precipitates in the hot stamping parts after hot stamping can also be satisfied.

[0055] In one embodiment, when the contents of titanium (Ti), niobium (Nb), vanadium (V), and molybdenum (Mo) contained in the steel sheet are respectively represented by [Ti], [Nb], [V], and [Mo] in weight %, the following [Inequality 1] may be satisfied.

[0056] [Inequality 1]

[0057] 0.015≤0.25([Ti]+[Nb]+[V]+0.25[Mo])≤0.060 (unit: weight %).

[0058] Therefore, the shape of the microstructure formed in the steel plate can be controlled. For example, the microstructure may include a region where a pearlite structure is locally accumulated (hereinafter referred to as a pearlite region). The region where the pearlite structure is accumulated will affect the grain size, fraction and roughness after hot stamping, which may reduce the hydrogen embrittlement resistance and bending angle (such as V-shaped bending angle) performance of the hot stamping parts after hot stamping. Therefore, in the steel plate before hot stamping, when the content of titanium (Ti), niobium (Nb), vanadium (V) and molybdenum (Mo) satisfies [Inequality 1], the grain refinement of the hot stamping parts after hot stamping can be easily controlled, thereby ensuring hydrogen embrittlement resistance and bending angle performance.

[0059] The microstructure of the steel plate before hot stamping may include ferrite and pearlite. In one embodiment, the steel plate may include ferrite with an area fraction of 50%-99% and pearlite with an area fraction of 0.1%-50%. In addition, the steel plate may include other inevitable structures. For example, the steel plate may include 0% or more and less than 5% of other inevitable structures. At the same time, in one embodiment, the average grain size of ferrite contained in the steel plate before hot stamping can be controlled to meet the range of 2μm or more and 10μm or less.

[0060] Carbon (C) and / or manganese (Mn) may segregate in pearlite, and therefore, the microstructure of the steel sheet for hot stamping may include pearlite with a relatively high carbon content and / or manganese content. In addition, pearlite with a relatively high carbon content and / or manganese content may locally accumulate in the steel sheet to form a pearlite region.

[0061] According to an embodiment of the present invention, the steel sheet before hot stamping can be controlled so that the size, density and area fraction of the pearlite region of the steel sheet for hot stamping meet the preset conditions, and at the same time contain the carbon content and manganese content optimized as described above. Therefore, the mechanical properties of the molded parts after hot stamping, such as tensile strength, yield strength, bending properties, elongation, etc., can be controlled.

[0062] The tensile strength of the hot stamping part formed by hot stamping the steel plate can meet the range of 1700MPa or more, especially 1760MPa or more and 1950MPa or less. In addition, the yield strength of the hot stamping part can meet the range of 1150MPa or more, especially 1200MPa or more and 1350MPa or less. In addition, the hot stamping part can meet the bending angle of 50° or more, and the elongation can be 5% or more. Here, the "bending angle" may mean a V-shaped bending angle in the rolling direction (rolling direction, RD).

[0063] The degree of influence on the mechanical properties of hot stamped parts after hot stamping can be different according to the carbon (C) content and manganese (Mn) content contained in the pearlite accumulated in the pearlite region in the steel plate before hot stamping. Specifically, the area where pearlite (containing 0.27 wt. % or more carbon and 1.0 wt. % or more manganese) is locally concentrated affects the mechanical properties of hot stamped parts. In contrast, the area where pearlite with a carbon content of less than 0.27 wt. % or a manganese content of less than 1.0 wt. % is locally concentrated has the least effect on the mechanical properties of hot stamped parts. Therefore, the steel sheet for hot stamping according to an embodiment of the present invention is controlled so that the size, density and area fraction of the area where pearlite containing 0.27 wt. % or more carbon and 1.0 wt. % or more manganese is locally concentrated meet the preset conditions.

[0064] The steel sheet for hot stamping according to an embodiment of the present invention may include a pearlite region in which pearlite containing 0.27 wt % to 0.70 wt % of carbon (C) and / or 1.0 wt % to 5.0 wt % of manganese (Mn) is locally accumulated. The size, shape, and area fraction of the pearlite region may be controlled to meet preset conditions.

[0065] In one embodiment, the average length of the pearlite region can be controlled to meet the range of 0.01 μm or more and 500 μm or less, particularly 0.1 μm or more and 100 μm or less. In addition, the average thickness of the pearlite region can be controlled to meet the range of 0.01 μm or more and 30 μm or less. In addition, the average gap between the pearlite regions can be controlled to be 0.01 μm or more and 10 μm or less.

[0066] In one embodiment, the area fraction of the pearlite region in the steel sheet for hot stamping may be controlled to satisfy the range of 0.1% or more and 15% or less.

[0067] The pearlite region may contain 50% or more pearlite and 5% or less ferrite by area fraction. In addition, optionally, up to 5% of low temperature phase structures (such as precipitates, martensite, and / or bainite, etc.) may be included.

[0068] Figure 2 To show that by Figure 1 An image of the structure of a hot stamped part formed by hot stamping a steel plate.

[0069] The hot stamping part may include martensite, bainite, ferrite and / or austenite. The proportion of the microstructure of the hot stamping part and the average grain size of the microstructure may be controlled to meet the preset conditions. Therefore, the mechanical properties of the hot stamping part, such as tensile strength, yield strength, bending performance, elongation, etc., may be controlled. For example, the tensile strength of the hot stamping part may meet the range of 1700MPa or more, in particular the range of 1760MPa or more and 1950MPa or less. In addition, the yield strength of the hot stamping part may meet the range of 1150MPa or more, in particular the range of 1200MPa or more and 1350MPa or less. In addition, the hot stamping part may meet the bending angle of 50° or more, and the elongation may be 5% or more.

[0070] In one embodiment, the microstructure of the hot stamped part may include 70% or more martensite, 30% or less bainite and ferrite, 5% or less retained carbides, and retained austenite.

[0071] In one embodiment, the microstructure included in the hot stamping part may be refined. Specifically, the average grain size of the microstructure included in the hot stamping part may be controlled to meet the range of 15 μm or less, particularly 2 μm or more and 15 μm or less.

[0072] Reference Figure 2 The hot stamped part according to the embodiment of the present invention may include a microstructure including austenite grains. The steel sheet may include a martensite phase having an area fraction of 70% or more, and the austenite grains may be generally distributed in the martensite phase.

[0073] In one embodiment, the average size of the austenite grains in the hot stamping part may be about 15 μm or less, particularly 13 μm or less. When the average size of the austenite grains exceeds 15 μm, fracture may occur during the hydrogen embrittlement evaluation process. By controlling the austenite grain size (AGS) in the hot stamping part below a certain level, the sensitivity to hydrogen embrittlement can be reduced. The austenite grain size can be controlled by elements that form precipitates in the steel sheet. For example, for a steel sheet containing niobium (Nb), titanium (Ti) and molybdenum (Mo), after hot stamping, the refinement of the austenite grains can be easily achieved in the hot stamping part. In addition, the steel sheet may further contain vanadium (V) other than niobium (Nb), titanium (Ti) and molybdenum (Mo).

[0074] Figure 3 and Figure 4 Graphs showing the results of measuring austenite grain size and fraction of hot stamped parts according to an embodiment of the present invention and comparative examples.

[0075] Specifically, Figure 3To measure the fraction of austenite grains having a size of about 10 μm or more in a hot stamped part according to an embodiment of the present invention, Figure 4 This is a graph measuring the fraction of austenite grains having a size of about 20 μm or more in a hot stamped part according to an embodiment of the present invention. Samples ① and ② are according to comparative examples, and samples ③ and ④ are according to an embodiment of the present invention. Samples ① and ② according to the comparative example fractured during the hydrogen embrittlement evaluation, while samples ③ and ④ according to an embodiment of the present invention did not fracture during the hydrogen embrittlement evaluation, satisfying the performance to be achieved by the present invention.

[0076] In one embodiment, the fraction of austenite grains having a size of about 10 μm or more in the hot stamped part may be 67% or less, specifically 65% ​​or less.

[0077] like Figure 3 As shown, the sample ① and the sample ② formed according to the comparative example satisfy that the fraction of austenite grains with a size of about 10μm or more exceeds 67%. The sample ① and the sample ② according to the comparative example fractured during the hydrogen embrittlement evaluation process, so it can be seen that the sample ① and the sample ② according to the comparative example did not achieve the performance to be achieved by the present invention. In contrast, the sample ③ and the sample ④ formed according to the embodiment of the present invention satisfy that the fraction of austenite grains with a size of about 10μm or more is 67% or less. The sample ③ and the sample ④ according to the embodiment of the present invention did not fracture during the hydrogen embrittlement evaluation process, so it can be seen that the performance to be achieved by the present invention is met. In other words, when the average size of austenite grains in the hot stamping part is about 15μm or less, and the formed sample satisfies that the fraction of austenite grains with a size of 10μm or more is 67% or less, the hydrogen embrittlement performance and the bending angle performance can be met.

[0078] In one embodiment, the fraction of austenite grains having a size of about 20 μm or more in the hot stamped part may be 10% or less, specifically 7% or less.

[0079] like Figure 4As shown, the sample ① and the sample ② formed according to the comparative example meet the fraction of austenite grains with a size of about 20μm or more exceeding 10%. The sample ① and the sample ② according to the comparative example fractured during the hydrogen embrittlement evaluation process, so it can be seen that the sample ① and the sample ② according to the comparative example did not achieve the performance to be achieved by the present invention. In contrast, the sample ③ and the sample ④ formed according to the embodiment of the present invention meet the fraction of austenite grains with a size of about 20μm or more of 10% or less. The sample ③ and the sample ④ according to the embodiment of the present invention did not fracture during the hydrogen embrittlement evaluation process, so it can be seen that the performance to be achieved by the present invention is met. In other words, when the average size of austenite grains in the hot stamping part is about 15μm or less, and the formed sample meets the fraction of austenite grains with a size of 20μm or more of 10% or less, the hydrogen embrittlement performance and the bending angle performance can be met. The sample ③ and the sample ④ formed according to the embodiment of the present invention can meet the average size of austenite grains in the hot stamping part of 13μm or less.

[0080] Meanwhile, the hot stamping parts according to an embodiment of the present invention may include precipitates, which contain at least one of niobium (Nb), titanium (Ti), molybdenum (Mo) and vanadium (V). Niobium (Nb), titanium (Ti), molybdenum (Mo) and vanadium (V) contained in the steel sheet are carbide-producing elements that contribute to the formation of precipitates. Titanium (Ti), niobium (Nb) and molybdenum (Mo) form carbon (C)-based precipitates, thereby ensuring the strength, hydrogen embrittlement and bendability of the hot stamping parts. These elements can be used as hydrogen trapping sites to effectively improve the delayed fracture resistance. In other words, the precipitates can be distributed in the steel sheet to capture hydrogen. In other words, the precipitates provide trapping sites for hydrogen introduced into the interior of the steel sheet before hot stamping, thereby improving the hydrogen-induced delayed fracture performance of the hot stamping parts.

[0081] As described above, the amount of niobium (Nb), titanium (Ti) and vanadium (V) contained may be 0.005 wt % to 0.06 wt %, respectively, and the amount of molybdenum (Mo) contained may be 0.05 wt % to 0.2 wt %. In particular, niobium (Nb), titanium (Ti), molybdenum (Mo) and vanadium (V) may satisfy the above [inequality 1]. In this case, as described above, the average size of austenite grains in the hot stamping part is about 15 μm or less, the fraction of austenite grains having a size of about 10 μm or more in the hot stamping part is 67% or less, and the fraction of austenite grains having a size of about 20 μm or more in the hot stamping part may be formed to be 10% or less. Therefore, the hydrogen embrittlement performance and bending angle performance of the hot stamping part may be satisfied.

[0082] The precipitation behavior of the precipitates can be measured by analyzing the transmission electron microscope (TEM) image method. Specifically, for the sample, TEM images of a specific area as many as a preset number can be obtained, and the precipitates can be extracted from the obtained images by an image analysis program, and the number of precipitates, the average distance between precipitates, the diameter of the precipitates, etc. can be measured for the extracted precipitates.

[0083] In addition, in the process of measuring the diameter of the precipitate, the shape of the precipitate is converted into a circle in consideration of the unevenness of the shape of the precipitate, thereby calculating the diameter of the precipitate. Specifically, the area of ​​the extracted precipitate can be measured using a unit pixel having a specific area, and the precipitate can be converted into a circle having the same area as the measured area, thereby calculating the diameter of the precipitate.

[0084] In one embodiment, the average particle size (size, diameter) of the precipitates can be controlled to meet the preset conditions. Specifically, the average particle size of the precipitates formed in the hot stamping part can be 10 nm or less, particularly 1 nm or more and 6 nm or less. In addition, the amount of activated hydrogen of the hot stamping part including the precipitates can be 0.6 wppm or less.

[0085] As a comparative example, when niobium (Nb), titanium (Ti) and vanadium (V) are each contained in excess of 0.06 wt %, or molybdenum (Mo) is contained in less than 0.05 wt %, the average grain size of the precipitates exceeds 10 nm, and thus the probability of hydrogen embrittlement occurring in the hot stamped parts may increase.

[0086] In one embodiment, the composition (i.e., average composition) of the precipitate may include 50 wt% or less of titanium (Ti) and 30 wt% or more of molybdenum (Mo). In order for the precipitate to satisfy the above average particle size, the composition of the precipitate satisfies 50 wt% or less of titanium (Ti) and 30 wt% or more of molybdenum (Mo). As a comparative example, when the composition of the precipitate contains more than 50 wt% of titanium, or less than 30 wt% of molybdenum, the precipitate becomes coarse, and thus the design strength may not be ensured.

[0087] In one embodiment, the gap (i.e., average distance) between adjacent precipitates can be controlled to meet a preset range. Here, the "average distance" can be measured by the average free path of the precipitate. Specifically, the average distance between the precipitates can be calculated using the particle area fraction and the number of particles per unit length. However, the method for measuring the precipitation behavior of the precipitate is not limited to the above examples, and various methods can also be used.

[0088] Specifically, the average distance between the precipitates may be 0.1 nm or more and 100 nm or less, particularly 0.1 nm or more and 50 nm or less, or 0.1 nm or more and 10 nm or less. When the average distance between the micro precipitates is less than 0.1 nm, the formability and bendability may be deteriorated. In contrast, when the average distance between the micro precipitates exceeds 100 nm, the strength may decrease.

[0089] In one embodiment, the average number of precipitates per unit area may be controlled to meet a preset condition. Specifically, when the above [Inequality 1] is satisfied, the refinement of the precipitates may be performed. In this case, the average number of precipitates per unit area may be 10,000 / 100 μm 2 Up to 35,000 / 100μm 2 As a comparative example, when the above [Inequality 1] is not satisfied, the precipitates are coarsened. In this case, the average number of precipitates per unit area may be less than 10,000 / 100 μm. 2 .

[0090] In the following description, the present invention is specifically described by embodiments and comparative examples. However, the embodiments and comparative examples described below are for more specific description of the present invention, and the scope of the present invention is not limited by the embodiments and comparative examples described below. Within the scope of the present invention, those skilled in the art may make appropriate corrections and modifications to the embodiments and comparative examples described below.

[0091] [Table 1]

[0092]

[0093] [Table 2]

[0094]

[0095] Table 1 shows the composition of the steel sheet for hot stamping, and Table 2 shows the measured values ​​for evaluating the austenite grain size and hydrogen embrittlement of the samples corresponding to the hot stamping parts. Comparative Examples 1 to 12 are samples whose values ​​do not satisfy [Inequality 1] in the composition of Table 1, and Embodiments 1 to 8 are samples corresponding to the hot stamping parts formed by hot stamping the steel sheet having the composition of Table 1.

[0096] Each sample was evaluated for hydrogen embrittlement using the ASTM G39-99 reference (4-point bending test) test method. Specifically, the sample was loaded in a four-point bending tester and a stress of 100% of the yield strength (YP) was applied to it. The sample was then immersed in an aqueous solution of 0.1N HCl for 100 hours and then measured for cracks, i.e., fractures, on the sample surface.

[0097] Referring to Table 2, Comparative Examples 1 to 12 are samples of hot stamping parts made of the following steel sheets: the steel sheets have a value of [Inequality 1] composed of Table 1 (i.e., 0.25 (Ti + Nb + V + 0.25Mo)) of 0.013 wt%, which is outside the range of 0.015 wt% to 0.060 wt%. Niobium (Nb), titanium (Ti), molybdenum (Mo) and vanadium (V) are carbide-producing elements that contribute to the formation of precipitates, and Comparative Examples 1 to 12 do not meet the precipitate control conditions, showing the result of coarsening of the austenite grain size in the hot stamping parts. Therefore, it can be seen that in Comparative Examples 1 to 12, the fraction of austenite grains having a size of 10 μm or more formed exceeds the reference value of 67% of the present invention. In addition, it can be seen that in Comparative Examples 1 to 12, the fraction of austenite grains having a size of 20 μm or more formed is about 50% or more, far exceeding the reference value of 10% of the present invention. Therefore, it can be seen that in Comparative Examples 1 to 12, fracture occurred in the hydrogen embrittlement evaluation, and thus the design conditions of the present invention were not satisfied.

[0098] At the same time, it can be seen that in Embodiment 1 to Embodiment 8 (embodiments of the present invention), while satisfying the composition of Table 1, the fraction of austenite grains having a size of 10 μm or more is 67% or less, and the fraction of austenite grains having a size of 20 μm or more is 10% or less. Therefore, it can be seen that in Embodiment 1 to Embodiment 8, no fracture occurs in the hydrogen embrittlement evaluation, thereby satisfying the design conditions of the present invention.

[0099] In contrast, Comparative Examples 13 to 16 are samples that satisfy the composition of Table 1, but do not satisfy the conditions of precipitates, etc. due to different process control conditions. In Comparative Examples 13 to 16, the fraction of austenite grains with a size of 10 μm or more formed exceeds 67%, and the fraction of austenite grains with a size of 20 μm or more formed exceeds 10%. Therefore, it can be seen that in Comparative Examples 13 to 16, fractures occurred in the hydrogen embrittlement evaluation, and thus the design conditions of the present invention were not satisfied.

[0100] In the above, although embodiments have been described, these are only examples, and those skilled in the art to which the present invention belongs may make various modifications and changes to these descriptions. Therefore, without departing from the spirit and scope of the present invention as defined by the following claims, various changes may be made to the form and details thereof.

Claims

1. A hot stamping component, comprising a steel plate, the steel plate comprising: 0.26 wt% to 0.40 wt% carbon (C), 0.02 wt% to 2.0 wt% silicon (Si), 0.3 wt% to 1.60 wt% manganese (Mn), 0.03 wt% or less phosphorus (P), 0.008 wt% or less sulfur (S), 0.05 wt% to 0.90 wt% chromium (Cr), 0.0005 wt% to 0.0006 wt% 0.01 wt % of boron (B), 0.05 wt % to 0.2 wt % of molybdenum (Mo), 0.001 wt % to 0.095 wt % of titanium (Ti), 0.001 wt % to 0.095 wt % of niobium (Nb), 0.001 wt % to 0.095 wt % of vanadium (V), the balance of iron (Fe) and other inevitable impurities, the hot stamping part having a tensile strength of 1700 MPa or more and a yield strength of 1150 MPa or more, in, The hot stamped part includes a microstructure including austenite grains and carbon-based precipitates, the carbon-based precipitates including at least one of niobium (Nb), titanium (Ti), molybdenum (Mo), and vanadium (V), and the austenite grains have an average size of 15 μm or less.

2. The hot stamped component according to claim 1, wherein: The fraction of austenite grains having a size of 10 μm or more is 67% or less.

3. The hot stamped component according to claim 1, wherein: The fraction of austenite grains having a size of 20 μm or more is 10% or less.

4. The hot stamped component according to claim 1, wherein: When the contents of titanium (Ti), niobium (Nb), vanadium (V), and molybdenum (Mo) contained in the steel sheet are respectively represented by [Ti], [Nb], [V], and [Mo] in weight %, the following [Inequality 1] is satisfied, [Inequality 1] 0.015≤0.25([Ti]+[Nb]+[V]+0.25[Mo])≤0.060 (unit: weight %).

5. The hot stamped component according to claim 1, wherein: The amount of active hydrogen of the hot stamped part was 0.6 wppm or less.

6. The hot stamped component according to claim 1, wherein: The average particle size of the precipitates was 10 nm or less.

7. The hot stamped component according to claim 1, wherein: The precipitate contains 50 wt % or less of titanium (Ti) and 30 wt % or more of molybdenum (Mo).

8. The hot stamped component according to claim 1, wherein: The average number of precipitates per unit area is 10,000 / 100 μm 2 Up to 35,000 / 100μm 2 .

9. The hot stamped component according to claim 1, wherein: The average gap between the precipitates is 0.1 nm to 100 nm.

10. The hot stamped component according to claim 1, It satisfies a bending angle of 50° or more.

Citation Information

Patent Citations

  • Hot stamping coating steel sheets and method of manufacturing the same

    KR1020170076009A

  • Method and apparatus for monitoring for interrupted transmission indication in a wireless communication system

    KR1020190095858A